1998
DOI: 10.1016/s0022-4405(97)00049-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Home and School Behavior Problems in Rural and Urban Settings

Abstract: This study examined the cross-situational patterns of behavior problems shown by children in rural and urban communities at school entry. Behavior problems exhibited in home settings were not expected to vary significantly across urban and rural settings. In contrast, it was anticipated that child behavior at school would be heavily influenced by the increased exposure to aggressive models and deviant peer support experienced by children in urban as compared to rural schools, leading to higher rates of school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
1
43
0
2
Order By: Relevance
“…However, the presence of children's mental and behavioral health problems is salient within rural America where, relative to their urban counterparts, children are more likely to have a mental health problem (Lenardson, Ziller, Lambert, Race, & Yousefian, 2010), demonstrate behavior difficulties at home (Hope & Bierman, 1998), and enter school with higher overall adjustment problems (Sheridan et al, 2014b). Our research has shown that even as young as Kindergarten, rural students have more challenging behaviors than non-rural students (Sheridan et al, 2014b), and the gap between rural and non-rural students in positive, adaptive behaviors increases with greater levels of risk (i.e., poverty, single parent, language barriers, low parental education).…”
Section: Implications For Practice In Rural Communitiesmentioning
confidence: 99%
“…However, the presence of children's mental and behavioral health problems is salient within rural America where, relative to their urban counterparts, children are more likely to have a mental health problem (Lenardson, Ziller, Lambert, Race, & Yousefian, 2010), demonstrate behavior difficulties at home (Hope & Bierman, 1998), and enter school with higher overall adjustment problems (Sheridan et al, 2014b). Our research has shown that even as young as Kindergarten, rural students have more challenging behaviors than non-rural students (Sheridan et al, 2014b), and the gap between rural and non-rural students in positive, adaptive behaviors increases with greater levels of risk (i.e., poverty, single parent, language barriers, low parental education).…”
Section: Implications For Practice In Rural Communitiesmentioning
confidence: 99%
“…Prior research has examined the affect of poverty within urban (i.e., living in densely populated areas) and rural (i.e., living in areas of low population density) communities on children's behavior problems (Conger et al, 2002;Hope & Bierman, 1998;Raver et al, 2009). However, less research has examined the association between community-level variables and protective factors in children (Hope & Bierman).…”
mentioning
confidence: 99%
“…For example, the fact that rural teachers perceived themselves has having less teaching social and emotional needs than urban teachers may be understood by the fact that students from rural and urban schools present different tendencies of behaviors problems (S. L. Bender, Fedor, & Carlson, 2011). Students from rural schools present more internalizing problems and students from urban schools tend to present more externalization problems (e.g., Hope & Bieman, 1999). Urban school teachers tend to present higher levels of stress and burnout as a result of the demands and efforts that students' problematic behaviors represent (Abel & Sewell, 1999), which may be understood to the dynamics between school and context characteristics and teachers individual characteristics (personality, perceptions) which result in several outcomes, such as teacher stress and burnout (CanoGarcia, Padilla-Munoz, & Carrasco-Ortiz, 2005).…”
Section: Discussionmentioning
confidence: 99%